Respuesta :
Answer:
Two solutions were found :
x =(-35-√1393)/14=-5/2-1/14√ 1393 = -5.166
x =(-35+√1393)/14=-5/2+1/14√ 1393 = 0.166
Step-by-step explanation:
Two real solutions:
x =(-35+√1393)/14=-5/2+1/14√ 1393 = 0.166
or:
x =(-35-√1393)/14=-5/2-1/14√ 1393 = -5.166
Two solutions were found :
x =(-35-√1393)/14=-5/2-1/14√ 1393 = -5.166
x =(-35+√1393)/14=-5/2+1/14√ 1393 = 0.166
Processing ends successfully
plz mark me as brainliest :)
First, get the x out of the denominators on both sides by multiplying the entire equation by 3x(x+5) because it's the LCM of both denominators
7/3x*3x(x+5) = 2/(x+5) * 3x(x+5) (The underlined bits cancel out because they're the same)
So now you have 7(x+5) = 2(3x)
From there, you can simplify it further.
7(x+5) = 2(3x)
7x + 35 = 6x
7x - 6x + 35 = 6x - 6x
x + 35 = 0
x + 35 - 35 = 0 - 35
x = -35
Tada!